BOPHYs versus BODIPYs: A comparison of their performance as effective multi-function organic dyes. (November 2019) - Sola-Llano, R.; Jiménez, J.; Avellanal-Zaballa, E.; Johnson, M.; Cabreros, T.A.; Moreno, F.; Maroto, B.L.; Muller, G.; Bañuelos, J.; Cerdán, L.; García-Moreno, I.; Moya, S. de la
Abstract: The computationally-aided photophysical and lasing properties of a selected battery of BOPHYs are described and compared to those of related BODIPY counterparts. The present joined theoretical-experimental study helps to put into context the weaknesses and strengths of both dye families under different irradiation conditions. The chemical versatility of the BOPHY scaffold has been also comparatively explored to modulate key photonic properties towards the development of red-emitting dyes, chiroptical dyes and singlet oxygen photosensitizers. Thus, BOPHY BINOLation by fluorine substitution with enantiopure BINOLs endows the BOPHY chromophore with chiroptical activity, as supporting by the simulated circular dichroism, decreasing deeply its fluorescent response due to the promotion of fluorescence-quenching intramolecular charge transfer (ICT). Interestingly, the sole alkylation of the BOPHY core strongly modulates the promotion of ICT, allowing the generation of highly bright BINOL-based BOPHY dyes. Moreover, 3, 3′-dibromoBINOLating BOPHYs can easily achieve singlet-oxygen photogeneration, owing to spin-orbit coupling mediated by heavy-atom effect feasible in view of the theoretically predicted disposition of the bromines surrounding the chromophore. From this background, we have established the master guidelines to design bright fluorophores and laser dyes, photosensitizers for singlet oxygen production and chiroptical dyes based on BOPHYs. The possibility to finely mix and balance such properties in a given molecular scaffold outstands BOPHYs as promising dyes competing with the well-settled BODIPY dyes. Graphical abstract: Image 1 Highlights: BOPHY vs BODIPY, comparison of their (chiro)photonic and (photo)stability behavior. Both outstand as versatile scaffolds with tunable and tailor made properties. Establishment of the structural guidelines ruling the (chiro)optics of BOPHYs. Bromobinolation, easy approach to yield chiral and fluorescence photosensitizers. BODIPY better photonic performance and stability than BOPHY.